2022
DOI: 10.1002/bse.3265
|View full text |Cite
|
Sign up to set email alerts
|

Green core competence and firm performance in a post‐conflict country, Iraq

Abstract: Green core competence theory proposes that green core competence is needed for green innovation performance and, in turn, firm performance. We demonstrate that this theory applies in post‐conflict Iraq where green innovation performance was conditional on commitment to sustainable management and development of green technology and skills. Data from 238 Iraqi executives showed that green product and process innovation performance increased with green core competence, but only when the firm invested in people an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 53 publications
1
22
0
Order By: Relevance
“…Finally, it was revealed that the relationship between the green core competencies of enterprises and green process innovation (β = 0.269, t; 3.338, p; 0.001) was positively significant, and H3 was supported according to this finding. This finding strengthens the results of the few studies in the literature and advances the theory Chen, 2008;Qu, Khan, Yahya, Zafar, and Shahzad, 2022;Al Halbusi, Klobas, and Ramayah, 2022). According to Ahmad et al (2022), when enterprises develop their green dynamic capabilities to a certain level, they display superior environmental performance by developing products and processes that are less harmful to the environment.…”
Section: Findings As a Results Of The Analysissupporting
confidence: 81%
“…Finally, it was revealed that the relationship between the green core competencies of enterprises and green process innovation (β = 0.269, t; 3.338, p; 0.001) was positively significant, and H3 was supported according to this finding. This finding strengthens the results of the few studies in the literature and advances the theory Chen, 2008;Qu, Khan, Yahya, Zafar, and Shahzad, 2022;Al Halbusi, Klobas, and Ramayah, 2022). According to Ahmad et al (2022), when enterprises develop their green dynamic capabilities to a certain level, they display superior environmental performance by developing products and processes that are less harmful to the environment.…”
Section: Findings As a Results Of The Analysissupporting
confidence: 81%
“…In their comprehensive literature review, [30] view business intelligence as a combination of policies, processes, cultures, and technologies used to store, manipulate, and analyze data. In addition, four main steps characterize business intelligence: system sources, data acquisition, data warehouse, and reporting and analysis [31,32].…”
Section: Business Intelligencementioning
confidence: 99%
“…Modern organizations face a more complex, fast-paced, and turbulent environment than ever before, such as facing the challenges of the new era of artificial intelligence and sustainability in post-epidemic era, with an alarmingly high failure rate for organizational change and innovation initiatives. [1][2][3][4] Several studies suggest that leaders and employees attribute different influences toward successful change. 5,6 Leadership has been identified as the main reason for the success or failure of team-based organizational systems, which are the basic functional units of an institution.…”
Section: Introductionmentioning
confidence: 99%